Familial partial lipodystrophy, mandibuloacral dysplasia and restrictive dermopathy feature barrier-to-autointegration factor (BAF) nuclear redistribution - Capanni, Cristina (Landes Bioscience, 2012)
Prelamin A processing impairment is a common feature of a restricted group of rare genetic alterations/disorders associated with a wide range of clinical phenotypes. Changes in histone posttranslational modifications, alterations in non-histone chromatin proteins and chromatin disorganization have been specifically linked to impairment of specific, distinct prelamin A processing steps, but the molecular mechanism involved in these processes is not yet understood . In this study, we show that the accumulation of wild-type prelamin A detected in restrictive dermopathy (RD), as well as the accumulation of mutated forms of prelamin A identified in familial partial lipodystrophy (FPLD) and mandibuloacral dysplasia (MADA), affect the nuclear localization of barrier-to-autointegration factor (BAF), a protein able to link lamin A precursor to chromatin remodeling functions. Our findings, in accordance with previously described results, support the hypothesis of a prelamin A involvement in BAF nuclear recruitment and suggest BAF-prelamin A complex as a protein platform usually activated in prelamin A-accumulating diseases. Finally, we demonstrate the involvement of the inner nuclear membrane protein emerin in the proper localization of BAF-prelamin A complex.